Adult moyamoya syndrome as a manifestation of varicella-associated cerebral vasculopathy: a case report - Rozi, Nur Raziana; Bahtiar, Mohamad Syahiirul Afifi; Hassan, Radhiana; Basiam, Sulaila (IIUM Press, 2023)
Moyamoya disease (MMD) is a rare cerebrovascular disorder characterized by progressive large intracranial artery narrowing and development of small vessel collaterals. Moyamoya syndrome (MMS) refers to the angiographic findings of MMD with predisposing medical conditions. Varicella-associated cerebral vasculopathy (VACV) is a severe complication of varicella zoster virus (VZV) infection and its association with MMS is rare in adult. We report on a case of a 55-year-old lady who presented with progressively worsening dysphasia and left lower limb weakness following a week of right herpes zoster ophthalmicus infection. The initial Magnetic Resonance Imaging (MRI) of brain demonstrated features of encephalitis with micro abscesses. Her serial repeated MRI brain imagings subsequently demonstrated worsening of cerebral infarctions with right internal carotid artery stenosis and basal ganglia collaterals suggestive of Moyamoya vasculopathy. This case highlights the rare association of VACV with MMS and should be considered as a potential serious complication in patients with VZV infection